2000
DOI: 10.1016/s0895-7061(99)00175-2
|View full text |Cite
|
Sign up to set email alerts
|

Electronic pill-boxes in the evaluation of antihypertensive treatment compliance: comparison of once daily versus twice daily regimen

Abstract: The objective was to compare the compliance of hypertensive patients treated with captopril twice daily or trandolapril once daily. After a 2-week placebo period, hypertensive patients (diastolic BP 95-115 mm Hg) were randomly allocated to trandolapril 2 mg once daily or to captopril 25 mg twice daily for 6 months. Trandolapril and captopril were packed in electronic pill-boxes equipped with a microprocessor that recorded date and time of each opening (MEMS). Patients' compliance was assessed both by standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
13

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 19 publications
2
39
1
13
Order By: Relevance
“…23,40 However, some other more recent studies reported compliance rates close to 90%. 46,47 Nuesch et al 47 discussed if higher compliance rates already reflected better acceptance of modern treatment with once daily regimes and comparatively mild side effects. The high compliance rate observed in our study could however be a result of increased awareness for compliance by completing the survey.…”
Section: Compliance In Hypertensive Patientsmentioning
confidence: 99%
“…23,40 However, some other more recent studies reported compliance rates close to 90%. 46,47 Nuesch et al 47 discussed if higher compliance rates already reflected better acceptance of modern treatment with once daily regimes and comparatively mild side effects. The high compliance rate observed in our study could however be a result of increased awareness for compliance by completing the survey.…”
Section: Compliance In Hypertensive Patientsmentioning
confidence: 99%
“…Pill counts are substantially less useful for assessing adherence in a clinic setting, where prescriptions can be filled at a variety of community pharmacies, and patients do not generally bring their medications to visits. In a research setting, medication containers with microprocessors record each time the container is opened, providing a surrogate measure of medication consumption (22)(23)(24). Notably, the event recorders may not agree fully with patient report of medication adherence (25).…”
mentioning
confidence: 99%
“…15 Patients on once-daily trandolapril had significantly better adherence compared to patients on twice-daily captopril treatment for hypertension, as measured using MEMS. 240 Self-report adherence was significantly higher in patients taking sustained-release nicardipine twice daily than conventional nicardipine three times daily. 241 Patients treated with a single combination tablet regimen for hypertension had significantly less cardiovascular events compared to those taking the components individually.…”
Section: Reminder Interventionsmentioning
confidence: 93%
“…There are many reminder interventions that have been implemented, including reminder phone calls, texts, pagers, interactive voice response systems and treatment simplification interventions. 130,220,[236][237][238][239][240][241][242][243] Reminder packaging (dose administration aids, dosette boxes and dose sachets) assembles medicine doses into days and/or times when the medication has to be taken. This has been shown to increase the proportion of doses taken, leading to a significantly reduced diastolic blood pressure and also HbA1c levels.…”
Section: Reminder Interventionsmentioning
confidence: 99%
See 1 more Smart Citation